Large‐Area Printing of Ferroelectric Surface and Super‐Domain for Solar Water Splitting. (9th February 2022) - Tian, Yu; Wang, Aiji; Wei, Yaqing; Pei, Minghui; Cao, Rongrong; Gu, Zhenao; Yuan, Qi; Hu, Yiwen; Wang, Jing; Liu, Kunhui; Shang, Dashan; Niu, Jiebin; et al.
Abstract: Surface electronic structures of the photoelectrodes determine the activity and efficiency of the photoelectrochemical water splitting, but the control of surface structures and interfacial chemical reactions remain challenging. Here, ferroelectric BiFeO3 is used as a model system to demonstrate a controllable water splitting reaction by large‐area constructing the hydroxyls‐bonded surface. The up‐shift of band edge positions at this ferroelectric surface enables and enhances the holes and electrons transfer through the hydroxyl‐active sites, leading to enhanced oxygen or hydrogen evolutions, respectively. Furthermore, the printing of ferroelectric super‐domain with microscale checkboard up/down electric fields enhances the photogenerated carriers separation and gives rise to an order of magnitude increase of the photocurrent. This large‐area printable ferroelectric surface and super‐domain offer an alternative platform for controllable and efficient photocatalysis. Abstract : Using ferroelectric BiFeO3 as a model system, a controllable water splitting via hydroxyls‐bonding is demonstrated. The up‐shift of band edge positions at this surface enables/enhances the holes/electrons transfer through the hydroxyl‐active sites, leading to the enhanced oxygen/hydrogen evolutions. Furthermore, the printing of ferroelectric super‐domain enhances the photogenerated carriers separation and gives rise to an order of magnitude increase of the photocurrent.